GREEN HUMAN RESOURCE MANAGEMENT: A REVIEW - Wahyu Wiguna; Ujo Sujoto; Martinus Tukiran; Syaefunnur Maszah (International Journal of Economy, Education and Entrepreneurship, 2023)
This review aims to explore organizations' green human resource management practices based on existing literature. Within this emerging field, it has generally been observed that the existing literature should be expanded further from the perspective of the Human Resource Management (HRM) function. The databases used are Google Scholar and Mendeley, limited to publications from 2015-2020. This review used 3 articles that fit the inclusion criteria. The results showed that environmental knowledge fully mediates the relationship between green HRM and EGB. What we need to criticize is that empirical evidence shows that the lack of efforts to implement GHRM, especially in the industrial sector, is proven to be still high levels of water pollution based on information from the Ministry of Environment and Forestry (KLHK) said that the water quality index in 2022 received a score of 53.88. This score increased from the previous year, which received a score of 52.82. Even so, the achievement of the value in 2022 has not met the target value of the water quality index, which is 55.03. and 2.5-micron particle air pollution, otherwise known as PM 2.5 in Indonesia in 2022, is reported to be the 26th worst globally